GEOLOGY STUDY OF POS BLAU AREA, GUA MUSANG WITH EMPHASIS ON DEPOSITIONAL ENVIRONMENT - B NIK HASSAN, NIK MOHAMAD EPI’ IFFAN (Universiti Teknologi PETRONAS, 2015)
Pos Blau is located within the Bentong Suture Zone that produced due tectonic movement, lead to collision of Sibumasu and Indochina terrain which generate subduction of retro ocean; Palaeo Tethys ocean beneath the continental margin. There is no indication of the subduction processes taking place whether beneath Sibumasu or Indochina but it is more likely preferred to Indochina correspond to the many reconstruction of subduction model. From that, it is believed that the some part of Palaeo Tethys ocean floor which lied between Sibumasu and Indochina terrains before the collision happen is preserved in the Bentong Suture Zone, where Pos Blau is located. Deep oceanic environment is the widest sedimentation area in the world. Despite being the widest area, it is not well explored because it’s rarely exposed in the surface like the shallow marine , fluvial, delta , or other sedimentation area. This system started from the shelf until the deep-sea basin. The availability of shale and mudstone in the Pos Blau area can be used to define the preserved part of Palaeo-Tethys ocean.